Effect of surfactants on SrM core–shell nanoparticles synthesised at low temperature. (1st May 2017) - Kumar, M. Rajesh; Hong, R.Y.
Abstract : Different morphology of surfactant capped SrFe12 O19 nanoparticles have been synthesised using the co‐precipitation method, by adding organic template (oxalic acid) as dispersant during citric acid addition. sodium hexametaphosphate and polyvinyl pyrrolidone used as capping agents. Calcinated surfactant capped SrFe12 O19 has been characterised using X‐ray diffraction, scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy analysis, Raman spectroscopy and vibrating sample magnetometer. The influence of the surfactants on the morphology of SrFe12 O19 core–shell nanoparticles was studied.